THE IMPORTANCE OF STUDYING ENVIRONMENTAL PROBLEMS FROM A PHILOSOPHICAL POINT OF VIEW - Naubetulaeva Elmira (World Scientific Research Journal, 2025)
Annotation: The role of philosophy in solving environmental problems, which are one of the global problems, and in improving people’s ecological knowledge and attitude towards nature is discussed.